Synthesis of Some Sulphonamido and Amino Alkanes and Their Antifungal Activity - Shinde, N.D.; Shinde, D.B.; Shingare, M.S. (Asian Journal of Chemistry, 2010)
A series of new substituted sulphonamido alkanes and amino alkanes have been prepared. The structures of these compounds were confirmed by spectral and analytical data. These compounds were screened for their antifungal activity.